BOTANICAL AND PHYTOCHEMICAL APPROACH ON PASSIFLORA SPP. – NEW NUTRACEUTICAL CROP IN ROMANIA - Tatiana Eugenia SESAN (Journal of Plant Development, 2016)
It has been performed a complex investigation – morpho-anatomical, physiological, taxonomical and phytochemical one – of Passiflora nutraceutical plants from Hofigal S.A., in the frame of project PN-II-PCCA-2013-4-0995, contract 160 (MAIA)/2014. Anatomic analysis of leaf lamina, petiole and stem, provided data with taxonomical importance, leading to the conclusion that plant material belongs to Passiflora caerulea L., in concordance with world monographers of Passiflora genus: VANDERPLANK (2000) and ULMAN & MacDOUGAL (2004). Physiological investigation referred to the following parameters: coefficient k, leaf area index (LAI), chlorophyll fluorescence, stomatal conductance and yield of green plant biomass. Phytochemical investigation consisted in analyzing active principles (polyphenols, flavonoids) content, in correlation with their antioxidant activity and determination of cytotoxicity of Passiflora extracts in NCTC cell line. At 10-150 µg/ml concentrations, it was recorded a normal cell morphology. At concentrations over 250 µg/ml, the plant extract become cytotoxic, altering the cell membrane structure, cells viability and proliferation.